2012
DOI: 10.1016/j.crohns.2011.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of MRSA, ESBL, and VRE colonization in the ambulatory IBD population

Abstract: Ambulatory IBD patients have similar prevalence of MRSA, ESBL and VRE compared to non-IBD controls. This finding suggests that the increased MRSA and VRE prevalence observed in hospitalized IBD patients is acquired in-hospital rather than in the outpatient setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
5
12
1
6
Order By: Relevance
“…In our single-centre study, we observed that the prevalence of MRSA and ESBL colonization on admission did not significantly differ between hospitalized IBD patients and non-IBD inpatients. This finding is consistent with our previous study of ARO prevalence among IBD ambulatory clinic patients and non-IBD controls recruited from the family practice clinics and emergency departments from the same tertiary centre (17). These findings are reassuring given previous reports that IBD patients incur a greater number of health care contacts and hospitalizations than the general population (18).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our single-centre study, we observed that the prevalence of MRSA and ESBL colonization on admission did not significantly differ between hospitalized IBD patients and non-IBD inpatients. This finding is consistent with our previous study of ARO prevalence among IBD ambulatory clinic patients and non-IBD controls recruited from the family practice clinics and emergency departments from the same tertiary centre (17). These findings are reassuring given previous reports that IBD patients incur a greater number of health care contacts and hospitalizations than the general population (18).…”
Section: Discussionsupporting
confidence: 92%
“…Two additional historical control groups were included in the analysis (17): one group of IBD patients from the ambulatory clinics at Mount Sinai Hospital recruited between July 15, 2010 and December 21, 2010; and a non-IBD cohort from the centre's affiliated family practice clinic recruited between June 15 and August 15, 2008 that was recruited as part of another MRSA prevalence study. The ambulatory IBD control group was used a comparator to assess potential differences in MRSA risk between the subgroup of IBD patients who required hospitalization and the broader ambulatory IBD population.…”
Section: Patient Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…18 We recently conducted a study of 306 ambulatory IBD patients from our tertiary referral center and found that the prevalence of MRSA colonization was 1.6% and similar to that of the non-IBD control group (1.5%) comprising individuals who attended the colon cancer screening program; the family practice unit; and the emergency department. 19 There may have been selection bias because this study included only clinic patients. It is possible that a select group of patients who did not attend clinics may have had higher rates of MRSA colonization.…”
Section: Tip Of the Iceberg?mentioning
confidence: 99%
“…27 To meet the demand of clinical medication for the treatment of digestive diseases caused by gastrointestinal bacterial infection, antibacterial drugs with diverse and novel structural origins are required.…”
Section: Antibacterial Activity and Sar Analysismentioning
confidence: 99%